Results of MCSHS Career Exploration Programs by Geography...National Society of Allied Health Annual Conference, March 30 - April 1, 2023, Montgomery, Alabama. - Dougherty, Margaret Papin; Knuttinen, Grace; Ausejo, David; Bello, Ruth; Hochstetler, Victoria; Prigge, Ryan; Renner, Amy Seegmiller; Young, Jolene (Journal of the National Society of Allied Health)
Purpose: Mayo Clinic School of Health Sciences (MCSHS) provides health science exploration programs for high school students. This study examined if high school students from Phoenix, Jacksonville, and Rochester (Minn.) were interested in the same health science professions. Methods: Students in the MCSHS programs participated in the study. The 2022 results of Mayo Clinic's 39-student CARES (Career Advancement, Research, and Education Summer) program (Phoenix); Mayo Clinic's 14-student Laboratory Medicine Sciences program (Jacksonville); 39-student CIP (Career Immersion Program) and 38-student RISE for Youth program (both in Rochester) were analyzed. Results: The majority of the participants verbalized that they were likely to pursue an allied health profession (physician assistant, pathologist's assistant, and/or surgical first assistant). The highest percentage of students likely to pursue allied health programs chose the Physician Assistant profession. Conclusion: Future studies can be improved by standardizing student applications, curriculum, program length, and evaluation methodology.